Determining dual-task costs and exploring interindividual responsiveness to an opponent using virtual reality - Pastel, S.; Schwadtke, A.; Krahmer, A.; Altrogge, K.; Bürger, D.; Heilmann, F.; Witte, K. (Frontiers in Virtual Reality, 2025)
IntroductionDual-task (DT) ability is essential in sports, where athletes must perform motor and cognitive tasks simultaneously. Virtual reality (VR), with its enhanced performance and affordability, offers a valuable tool for training and assessing these abilities. This study aimed to develop VR scenarios to measure DT costs and compare DT ability between athletes from individual (IG) and team (TG) sports using a basketball-specific scenario.Methods29 participants completed two experiments to examine DT ability: a reaching and a dribbling task (DR). The reaching involved three tasks: walking a 4-m track, standing while reacting to popping balls, and a combination of both. Parameters such as step length, gait time, and reaction were measured. In DR, participants dribbled while reacting to a virtual opponent. Data on conduction time, errors, reaction time, gaze behavior (GB), and decision-making were analyzed.ResultsSignificant differences were found between single and DT performances, with DT costs reaching up to 20% (p > 0.05). However, no significant differences were observed between IG and TG for selected parameters (F (1, 28) = 1.104, p = 0.410, partial η2 = 0.380).DiscussionDifferences in GB and decision-making were noted and discussed. VR proved effective in assessing DT costs and providing insights into decision-making processes.